Organizational Crisis Communication: Suboptimal Crisis Response Selection Decisions and Behavioral Economics. Issue 3 (4th March 2019) - Claeys, An-Sofie; Coombs, W Timothy
Abstract: Organizations in crisis often fail to select the optimal crisis response strategy, preferring strategies that avoid short-term losses over the ones that offer long-term gains. This article proposes a descriptive theory of behavioral crisis communication that uses principles of behavioral economics to explain the recurrence of suboptimal anomalies found in crisis communication. Based on decision-making literature we first argue that the distinct context in which crisis communication takes place (e.g., time pressure, information overload) determines whether or not decisions are made in an analytical or an intuitive manner. Behavioral economics further allows us to explain how intuitive decisions can sometimes be biased by heuristics, which can result in the choice for a suboptimal crisis response strategy in the heat of the moment.